Tackling antibiotic resistance in India. Issue 12 (December 2014) - Wattal, Chand; Goel, Neeraj
<x xml:space="preserve">Abstract</x> Infectious diseases are major causes of mortality in India. This is aggravated by the increasing prevalence of antimicrobial resistance (AMR) both in the community and in hospitals. Due to the emergence of resistance to all effective antibiotics in nosocomial pathogens, the situation calls for emergency measures to tackle AMR in India. India has huge challenges in tackling AMR, ranging from lack of surveillance mechanisms for monitoring AMR and use; effective hospital control policies; sanitation and non-human use of antimicrobial. The Ministry of Health and Family Welfare of Govt. of India has taken initiatives to tackle AMR. Extensive guidelines have been drafted and a model worksheet has been developed as a roadmap to tackle AMR.